2023
DOI: 10.1002/yea.3891
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular presence and genetic relationship of Helicobacter pylori within neonates' fecal yeasts and their mothers' vaginal yeasts

Tingxiu Yang,
Yuanyuan Zhang,
Hua Zhang
et al.

Abstract: Helicobacter pylori are transmissible from person to person and among family members. Mother‐to‐child transmission is the main intrafamilial route of H. pylori transmission. However, how it transmits from mother to child is still being determined. Vaginal yeast often transmits to neonates during delivery. Therefore, H. pylori hosted in yeast might follow the same transmission route. This study aimed to detect intracellular H. pylori in vaginal and fecal yeasts isolates and explore the role of yeast in H. pylor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The transmission of H. pylori can occur through person-to-person routes, especially within families where maternal-child transmission is prevalent ( Yang et al, 2023 ). Studies have shown that H. pylori infection can occur in clusters in families.…”
Section: Study On Helicobacter Pylori Infectionmentioning
confidence: 99%
“…The transmission of H. pylori can occur through person-to-person routes, especially within families where maternal-child transmission is prevalent ( Yang et al, 2023 ). Studies have shown that H. pylori infection can occur in clusters in families.…”
Section: Study On Helicobacter Pylori Infectionmentioning
confidence: 99%
“…H. pylori -specific 16S rDNA, cagA gene fragments, and H. pylori -specific antigens were still detectable, and some H. pylori 16S rDNA-positive Candida strains exhibited urease activity. We previously published a paper titled “Intracellular presence and genetic relationship of Helicobacter pylori within neonates’ fecal yeasts and their mothers’ vaginal yeasts”[ 9 ].…”
Section: To the Editormentioning
confidence: 99%
“…To our knowledge, we agree with the proponents that IgY- H. pylori demonstrated precise and specific interactions with H. pylori antigens. Our current study utilized IgG- H. pylori to detect H. pylori antigens in vaginal Candida and fecal Candida isolated from mothers and their newborns, respectively[ 9 ], as well as in gastric Candida strains isolated from patients. Our results showed that H. pylori antigen in Candida subcultures could be detected using immunofluorescence microscopy.…”
Section: To the Editormentioning
confidence: 99%